A Meta-Analysis of Tea Drinking and Risk of Parkinson's Disease - Feng-Jiao Li; Hong-Fang Ji; Liang Shen (The Scientific World Journal)
Background. Many studies have reported an association between tea drinking and Parkinson's disease (PD). Our purpose is to summarize the available information and evaluate the risk of PD associated with tea drinking. Methods. We searched all publications in English language on the association of tea drinking and PD risk published up to December 2010. The pooled analysis was performed with Review Manager 5.0. Results. In total, eight articles including 1418 cases and 4250 controls were included in the meta-analysis. The pooled odds ratio (95% CI) was 0.85 (0.74–0.98), which suggests the protective effect of tea drinking in PD risks. Moreover, the summary OR (OR: 0.83, 95% CI = 0.69–0.99) for drinkers of ≤1 cup of tea per day versus nonconsumers and that (OR: 0.96, 95% CI = 0.73–1.27) for drinkers of >1 cups of tea per day versus nonconsumers showed that there was not an apparent dose-response relationship. No indication for publication bias was found. Conclusions. This meta-analysis showed that tea drinking can lower the risk of PD, while no apparent dose-response relationship was found. Further effort is needed to fully understand the mechanism underlying the beneficial effect of tea consumption in lowering PD risk.